Management for hemobilia after hepatobiliary surgery - Jiang, Kai (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2003)
OBJECTIVE: To investigated the diagnosis and treatment for hemobilia after hepatobiliary surgery